Tool of KGB operational activity – conspirational flats. - Okuličiūtė, Lina (Genocidas ir rezistencija, 2008)
Based on the archival sources of the KGB of the Lithuanian SSR, the publication analyses the specificity of the purpose of the KGB’s tools of agent-operative work – meeting apartments and the tendencies of their use. In essence, it reveals the general nature of the KGB’s agent-operative activities in the meeting apartments, reviews the role of the apartment keepers, examines the possibilities of conspiratorial communication between the KGB operatives and the agency, which were carefully concealed from the Lithuanian public, and discusses the issue of maintenance of the secret KGB apartments and the settling of accounts with the apartment keepers.